Influence of compatibilizer and multifunctional additive loadings on flame retardation, plasticization, and impact modification of polylactide and poly(butylene adipate‐co‐terephthalate) biodegradable blends. (11th June 2020) - Phetwarotai, Worasak; Suparanon, Tunsuda; Phusunti, Neeranuch; Potiyaraj, Pranut
Abstract : The poor compatibility and flame retardation of polylactide (PLA) and poly(butylene adipate ‐co‐ terephthalate) (PBAT) blends seriously limit their applications. This study focused on the mechanical properties and flame retardancy of a PLA/PBAT blend under the influence of different levels of compatibilizer and multifunctional additives (MFA). PLA and PBAT were successfully compatibilized via reactive blending in a twin‐screw extruder. The flame retardation, flexibility, and impact toughness of the compatibilized blend were improved by the presence of tricresyl phosphate (TCP) and triethyl citrate (TEC). Separately and in combination, the two additives played crucial roles in flame retardant effectiveness, plasticization, and impact modification. The compatibilized blend displayed a UL‐94 V‐0 rating and exhibited a high limiting oxygen index (LOI). A slight reduction in thermal stability was exhibited when 20 phr TCP was incorporated into the blend. During combustion, an integrated char layer formed on the compatibilized blend surface and retarded flammability. The combination of TCP and TEC not only significantly improved dripping behavior and flame‐retardant properties of the compatibilized blend but also cooperatively enhanced the elongation at break and impact strength without impacting tensile strength, Young's modulus, LOI value, and thermal stability. The failure behavior of the blend changed from brittle to ductile, as evidenced by SEM, which revealed elongated fibrils after tension. These characteristics were associated with the presence of the MFAs and the improved interfacial adhesion between PLA and PBAT. As a result, flame retardation, flexibility, and impact resistance were enhanced. These improvements permit the wider application of PLA, especially in the electronic and automotive fields. Highlights: Compatibilized PLA/PBAT blend achieved the V‐0 rating and had a high LOI. Both TCP and TEC could be used as multifunctional additives (MFAs) in the compatibilized blend. Combination of MFAs synergistically enhanced elongation at break and impact strength without impacting other properties of the blends. These improvements permit the wider application of PLA, especially in the electronic and automotive fields.